Design and Develop a Web-Based Criminal Information System for the Criminal Investigation Unit at Police Sub-District XYZ - Hermawan, Diki; Sudarsono, Bernadus Gunawan; Sharyanto, Sharyanto (Yayasan Bina Internusa Mabarindo, 2024)
The current advancement of information technology significantly supports the optimization of law enforcement performance. The aim of this research is to design and develop a web-based criminal information system for the Criminal Investigation Unit (Reskrim) at the XYZ Metropolitan Police Station. This system is intended to facilitate the management of criminal case data, from reporting and recording to monitoring the progress of cases in a more effective and efficient manner. The system design is carried out using the Unified Modeling Language (UML) method to model the system's requirements and interactions, including Use Case diagrams, Activity Diagrams, and class diagrams. The implementation of this web-based system enables authorized users to access real-time data and provides integrated reporting features to support the investigation process. With the existence of this system, it is expected that the performance of the XYZ Metropolitan Police Station's Criminal Investigation Unit can be more optimal in carrying out law enforcement duties.